Practice Theory in Language Learning. (13th February 2013) - Young, Richard F.; Astarita, Alice C.
Abstract : Ortega (2011) has argued that second language acquisition is stronger and better after the social turn. Of the post‐cognitive approaches she reviews, several focus on the social context of language learning rather than on language as the central phenomenon. In this article, we present Practice Theory not as yet another approach to language learning, but as a philosophical and methodological frame within which the interplay between social context and language learning can be understood. We review the work of Bourdieu, de Certeau, Foucault, Giddens, and Goffman, who argue for the centrality of practice in human semiosis. Through analysis of introspective accounts by ten first‐generation/working class students of their foreign language learning experiences, we show how Practice Theory reveals a dialectic between the immediate experiences of language learners and the durable and transposable dispositions emanating from and integrating their past experiences.